1996
DOI: 10.1046/j.1464-410x.1996.82511.x
|View full text |Cite
|
Sign up to set email alerts
|

A 12‐month study of the placebo effect in transurethral microwave thermotherapy

Abstract: Objective To determine the placebo effect of trans-groups; 62% and 18% of patients had a >50% improvement in symptom score in the treated and urethral microwave thermotherapy (TUMT) in the treatment of benign prostatic enlargement (BPE).sham groups, respectively (P=0.001). The corresponding changes in flow rate were 36% and 11% Patients and methods A prospective, randomized shamcontrolled study in 93 patients (mean age 65, range (P=0.002), respectively. After 1 year, 63 patients were divided into those that ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(32 citation statements)
references
References 3 publications
0
31
0
1
Order By: Relevance
“…125,126,133,159,160,170,172,173 Six of those reported IPSS/AUA scores. 125,126,159,160,170,173 In all studies, IPSS/AUA scores were superior in the TUMT group and this was statistically significant in all six studies (p < 0.05).…”
Section: Symptom Scores At 3 Monthsmentioning
confidence: 99%
See 2 more Smart Citations
“…125,126,133,159,160,170,172,173 Six of those reported IPSS/AUA scores. 125,126,159,160,170,173 In all studies, IPSS/AUA scores were superior in the TUMT group and this was statistically significant in all six studies (p < 0.05).…”
Section: Symptom Scores At 3 Monthsmentioning
confidence: 99%
“…A total of 1209 participants were randomised across 11 eligible RCTs reported in 21 papers. 125,126,133,143,159,160,[170][171][172][173][174][219][220][221][222][223][224][225][226][227][228] Three studies took place in the US, 126,159,170 Although all 11 studies gave some details of the ages of participants, three gave only the mean or median age of the participant group as a whole, regardless of which intervention to which they were randomised. 160,171,174 Of the studies reporting IPSS/AUA scores at entry, 475 (74%) participants allocated to TUMT had severe symptoms of BPE and 60 (9%) had moderate symptoms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies using the older software (Prostasoft v2.0) reported acceptable symptomatic effect, better than sham treatment [12], and comparable with TURP [13]. However, with this software the ability of TUMT to reduce infravesical obstruction is clearly limited, and some studies have shown limited durability of the symptomatic response in a high proportion of patients, as re-treatment rates within 2-3 years of 43-48% have been reported [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…The criteria for a successful treatment outcome as recommended by the US Food and Drug Administration indicate that there should be an adequate proportional change as well as in absolute values overall. To allow the results of different studies to be compared, de Wildt et al [19] suggested that a 50% improvement should be the criterion for a successful treatment outcome of TUMT. Nevertheless, in a previous study where we compared 30 or 60 min of TUMT to sham treatment, the improvement was o30% for storage symptoms and was closely related to what the patients perceived as a successful outcome [3].…”
Section: Methodsmentioning
confidence: 99%